Density and distribution of western chimpanzees around a bauxite deposit in the Boé Sector, Guinea‐Bissau. Issue 9 (13th September 2019) - Dias, Filipe S.; Wenceslau, José F. C.; Marques, Tiago A.; Miller, David L.
Abstract: The Boé sector in southeast Guinea‐Bissau harbors a population of western chimpanzees ( Pan troglodytes verus ) that inhabits a mosaic of forest and savanna. The Boé sector contains a substantial bauxite deposit in a region called Ronde Hill, and there are plans for the construction of a mine, which may endanger the chimpanzee population. In 1‐week survey in May 2013, we used the standing crop nest counts method to obtain the number of chimpanzee nests and from that estimate the density and abundance of chimpanzees. We carried out five 1‐km line transects that covered the bauxite deposit and surrounding valleys. We used density surface modeling to analyze habitat preferences, then predicted chimpanzee nest density and distribution based on environmental variables. We found the projected location of the mine partially coincides with an area of high predicted abundances of chimpanzee nests and is surrounded by highly suitable areas for chimpanzees (northeast and southwest). We conclude the mine could have significant direct and indirect effects on this population of chimpanzees whose impacts must be carefully considered and properly mitigated if the mine is built. Abstract : Predicted abundance of nests overlaid with the location of the transects (black lines), location of clusters of nests (red dots), and future location of the mine (pink line). Ronde hill is shown by the green line and rivers are shown by blue lines. Research Highlights: Approximately 18 nest building western chimpanzees inhabit the surroundings of a bauxite deposit in the SW of Guinea‐Bissau; The construction of a mine can have adverse direct and indirect effects on this population.